(untitled) (Journal of Forensic Medicine & Toxicology, 2013)
One bullet is enough to kill a person but sometimes more than one bullet is required to do the job. However, one bullet killing multiple persons is very rare. The present report deals with this rare entity where one bullet fired from a rifle hit 3 persons and killed two of them. The deceased was travelling in an overcrowded bus on 15/7/ 11, when he was hit by a stray bullet which passed through two persons before hitting him. A passenger, who was sitting on the floor of the bus, a head constable of Chattisgarh police station, shot himself in the chest with an AK 47 rifle. The bullet after passing through the chest of the constable entered the groin of the boy who was sitting immediately behind him on the bus seat, and then hit the deceased. This case is also rare as it was a case of suicide in an unusual place i.e. an overcrowded bus with ample eyewitnesses.